Cardiorenal Syndromes and Sepsis. (22nd February 2011) - Chelazzi, C.; Villa, G.; De Gaudio, A. R.
Abstract : The cardiorenal syndrome is a clinical and pathophysiological entity defined as the concomitant presence of renal and cardiovascular dysfunction. In patients with severe sepsis and septic shock, acute cardiovascular, and renal derangements are common, that is, the septic cardiorenal syndrome. The aim of this paper is to describe the pathophysiology and clinical features of septic cardiorenal syndrome in light of the actual clinical and experimental evidence. In particular, the importance of systemic and intrarenal endothelial dysfunction, alterations of kidney perfusion, and myocardial function, organ "crosstalk" and ubiquitous inflammatory injury have been extensively reviewed in light of their role in cardiorenal syndrome etiology. Treatment includes early and targeted optimization of hemodynamics to reverse systemic hypotension and restore urinary output. In case of persistent renal impairment, renal replacement therapy may be used to remove cytokines and restore renal function.